The Relationship Of Pubter Women's Knowledge And Perineal Wound Care At The Atikah Midwifery Clinic, Panyabungan District, Kota, Mandailing Natal District - Ester Selfia Napitupulu; Ferika Desi (Sean Institute, 2023)
Caring for perineal wounds is one part that must be done to prevent infections in the vulva and perineum area caused by bacteria. And improper care of the perineum really supports the growth of bacteria that cause infections in the perineum. Good and correct care for perineal wounds avoids infections, complications, and post-partum maternal death. The aim of this study was to determine the relationship between postpartum mothers' knowledge and perineal wound care at the Atikah midwife clinic, Panyabungan subdistrict, Mandailing Natal district. The type of research used was analytical survey research with a cross section approach, the sample size was 37 people, the instrument used was a questionnaire. The results of the analysis prove that the majority of mothers have sufficient knowledge, 19 people (51.4%), while the minority are mothers with good knowledge, 4 people (10.8%) and 14 people who don't know enough (37.8%). The research results show that there is a relationship between knowledge and age (p value = 0.039), knowledge based on education (p value = 0.001), knowledge based on parity (p value = 0.031), knowledge based on work 0.019), knowledge based on information sources (p value = 0.018) postpartum mothers with perineal wound care at the Atikah midwife clinic, Panyabungan sub-district, Mandailing Natal district. In conclusion, from the research results it is known that the majority had a sufficient level of knowledge, 19 people (51.4%), while the minority were mothers with good knowledge, 4 people (10.8%). The conclusion of this study is that there is a significant relationship between postpartum mothers' knowledge and perineal wound care. It is hoped that health workers need to increase education for postpartum mothers about how to care for perineal wounds properly and correctly in order to prevent the proliferation of bacteria that cause infections in the perineum.